2016
DOI: 10.1111/aji.12474
|View full text |Cite
|
Sign up to set email alerts
|

The Multifaceted Actions of Leukaemia Inhibitory Factor in Mediating Uterine Receptivity and Embryo Implantation

Abstract: CitationRosario GX, Stewart CL. The multifaceted actions of leukaemia inhibitory factor in mediating uterine receptivity and embryo implantation. Am J Reprod Immunol 2016; 75: 246-255 doi:10.1111/aji.12474 Embryo implantation is mediated by the combined actions of the ovarian hormones E 2 and P4 on the uterus. In addition, the pro-inflammatory cytokine, leukaemia inhibitory factor (LIF), plays a pivotal role in regulating uterine receptivity. LIF is expressed in the endometrial glands and has a robust ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
68
2
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(76 citation statements)
references
References 86 publications
2
68
2
1
Order By: Relevance
“…However, its functions are not limited to inflammation: LIF has been demonstrated to play a crucial, non-redundant role in embryo implantation in both mice and humans [44-46]. LIF also maintains stem cells and regulates differentiation of germ cells [47, 48].…”
Section: Introductionmentioning
confidence: 99%
“…However, its functions are not limited to inflammation: LIF has been demonstrated to play a crucial, non-redundant role in embryo implantation in both mice and humans [44-46]. LIF also maintains stem cells and regulates differentiation of germ cells [47, 48].…”
Section: Introductionmentioning
confidence: 99%
“…19,42 LPA3 signaling is highly dependent on female sex hormones, P4 and E2. 19,42 LPA3 signaling is highly dependent on female sex hormones, P4 and E2.…”
Section: Btg and Kw Respectively Protect The Decrease Of Lpa3 In mentioning
confidence: 99%
“…Under the influence of ovarian hormones, several VEGF upstream molecules have been proved to participate in the process of early fetal-maternal interaction. [17][18][19] Studies have identified that vascular remodeling is fundamental at the maternal-fetal interface and LPA3 participates in the process of vascularization. 16 Previous results revealed that receptive state in the mouse uterus depends on LIF, which activates Janus kinase-signal transducer and activator of transcription 3 pathway and thus affects a cascade of events including angiogenesis therefore engaging in embryo implantation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Decidualization is one of the most important post‐implantation events that support embryonic development and provide nutrients until a functional placenta is formed (50, 51). Primarily induced by P4, endometrial stromal cells differentiate into secretory decidual cells at the time of blastocyst attachment to the uterine epithelium (52).…”
Section: Involvement Of Sgk1 In Decidualizationmentioning
confidence: 99%